Incidence and risk factors of hepatocellular carcinoma in patients with hepatitis C who achieved a sustained virological response through direct‐acting antiviral agents among the working population in Japan. Issue 6 (18th May 2022) - Hagiwara, Hideki; Ito, Yoshiki; Ohta, Takashi; Nozaki, Yasutoshi; Iwamoto, Takayuki; Hosui, Atsushi; Hiramatsu, Naoki; Tahata, Yuki; Sakamori, Ryotaro; Hikita, Hayato; Hayashi, Norio
Abstract: Background and Aim: The development of hepatocarcinogenesis after a sustained virological response (SVR) remains an important issue affecting the balance between treatment and occupational life of workers with chronic hepatitis C virus (HCV) infection in Japan. Here, we aimed to evaluate the hepatocellular carcinoma (HCC) reducing effect and risk factors for developing HCC after SVR in patients treated with direct‐acting antiviral agents (DAAs) among the working population. Methods: We studied 2579 working patients with chronic HCV infection who achieved SVR after antiviral treatment. We compared the difference in the cumulative incidence of post‐SVR HCC between the interferon (IFN)‐based n  = 1615 and DAA ( n  = 964) groups. The risk factors for post‐SVR HCC development were determined in the DAA group. Results: After propensity score matching ( n  = 644 in each group), the HCC development rates were not significantly different between the groups ( P  = 0.186). Multivariate Cox regression and the cutoff values determined by the receiver operating characteristic curve analyses revealed that age ≥61 years, diabetes, lower serum albumin levels <4.0 g/dL at 24 weeks after the end of treatment (EOT), and higher serum α‐fetoprotein levels ≥4.1 ng/mL at 24 weeks after the EOT were associated with the development of HCC. Conclusion: The HCC suppressing effect after SVR through DAA treatment is equivalent to that of IFN treatment in patients in the working population. Intensive follow‐up is required after SVR with DAA treatment in Japanese workers with these risk factors to ensure the promotion of health and employment support. Abstract : After propensity score matching ( n  = 644 in each group), the hepatocellular carcinoma (HCC) development rates were not significantly different between the interferon‐based and direct‐acting antiviral groups. Multivariate Cox regression and the cutoff values determined by the receiver operating characteristic curve analyses revealed that age ≥61 years, diabetes, lower serum albumin levels <4.0 g/dL at 24 weeks after the end of treatment (EOT), and higher serum α‐fetoprotein levels ≥4.1 ng/mL at 24 weeks after the EOT, were associated with the development of HCC.